A Controller for Delta Parallel Robot Based on Hedge Algebras Method. (17th January 2023) - Bui, Thanh-Lam; Nguyen, Thanh-Hung; Nguyen, Xuan-Thuan
Abstract : Based on the Hedge Algebras (HA) methodology, this paper presents a method for managing the trajectory of a delta robot. This technique is easily applied to existing devices in the process control domain. In the proposed control method, the semantically quantitative mapping may replace the verbal values of the fundamental rule in an analogous manner (SQM). Consequently, the basic rule may be represented as a three-dimensional numerical grid with linear interpolations. Compared to the Fuzzy Logic controller, it reduces the controller's complexity. In addition, when the control strategy is applied in reality, the system's response time is decreased. The simulation results indicate that the proposed technique is more exact than previous approaches. The experimental results reveal that the proposed technique is effective for robot trajectory tracking difficulties.